Identification of potent cholecystokinin-B receptor antagonists: synthesis, molecular modeling and anti-cancer activity against pancreatic cancer cells12. Issue 7 (4th July 2017) - Kumari, Saroj; Chowdhury, Joyita; Sikka, Manisha; Verma, Priyanka; Jha, Prakash; Mishra, Anil K.; Saluja, Daman; Chopra, Madhu
Abstract : Treatment of pancreatic cancer through CCK-BR antagonists is being suggested that suppress the growth promoting effects of gastrin. Abstract : Advanced malignant stages of pancreatic cancer have poor prognosis and very few treatment strategies are available. Pancreatic cancer is known to possess unique growth-related receptors that when activated, stimulate tumour proliferation. Gastrin and its related peptide cholecystokinin (CCK) are also significantly involved in the growth of this cancer type as well as other malignancies through activation of the cholecystokinin-B receptor (CCK-BR). New treatment strategies with CCK-BR antagonists are being suggested that suppress the growth promoting effects of gastrin. In this paper, we report the development of two series of quinazolinone derivatives incorporating hydrazinecarbothioamide (compounds3a–g ) and the hydrazino group (compounds4a–e ) as linkers for developing CCK-BR antagonists. The affinities of the compounds were determined using docking into the CCK-BR homology modeled structure. The compounds were tested for in vitro CCK-BR binding and gastric acid secretion in an isolated lumen-perfused mouse stomach assay. The compounds exhibited CCK-BR binding activity (IC50 ) in the range of 0.2–975 nM and showed good gastric acid secretion inhibitory activity. Molecular modeling of the compounds was done and pharmacophore mapping results showed good prediction of in vitro activity which correlated well with the experimental antagonistic activity. The compounds were further tested for their cytotoxicity on CCK-BR expressing pancreatic cancer cells. The results of the study provided two potent CCK-BR antagonists which also possess good to moderate growth inhibitory activities against pancreatic cancer cells.